Exercise physiology. Integrating theory and application - Kraemer, W. J.; Fleck, S. J.; Deschenes, M. R. (Wolters Kluwer, 2016)
This book will help students to develop an understanding of exercise physiology concepts and their application athletic performance and well-being with Exercise Physiology, 2e. Using an engaging evidence-based approach that combines research and theory with practical discussions of nutrition and training, the authors help students understand how the human body works and responds to exercise.